Rural healthcare enterprises in the vortex of COVID-19: The impact of public policies on the internal and external environment - Nikolaos Apostolopoulos; Sotiris Apostolopoulos; Ilias Makris; Stavros Stavroyiannis (Administrative Sciences, 2021)
The public policies implemented in order to contain the spread of COVID-19 in the community have created issues both in the internal and the external environments of the Greek rural healthcare enterprises. This study aimed to investigate the full extent of the issues (internal and external) caused by the public policies. Regarding the external factors, we examined the state, the local authorities, the financial institutions, the social stakeholders and the citizens. Regarding the internal factors, we focused on turnover, liquidity, working conditions, internal changes related to patient care and the implementation of protective measures. A qualitative research was conducted among twelve rural healthcare business owners in the form of semi-structured interviews. The research was conducted in the fall of 2020 during the second phase of COVID-19. The research showed that these enterprises were severely impacted by the government's public policies. Local authorities were not involved due to lack of competence. The business owners were unwilling to support their enterprises via bank lending. During the first phase of COVID-19, citizens postponed nonessential medical examinations, causing a reduction in these enterprises' turnover. As a result, in the following periods, these enterprises faced liquidity problems. However, they developed social objectives and implemented protective measures for their employees and patients. The present study contributes to the mapping of the factors affecting the internal and external environments of rural healthcare enterprises along with the public policies developed in times of prolonged crisis. These kinds of data are crucial to the business world and government officials voting on social policies. One cannot rule out the possibility of a new financial or health crisis; the findings of this study can prove to be a useful tool in the process of decision making.
Keywords: 350; COVID-19; healthcare enterprises; rural areas